FORMATION OF THE OF PROFESSIONAL COMPETENCE OF SPECIALISTS EMPLOYMENT CENTERS: THE TECHNOLOGICAL APPROACH - Voliyrska, Olena S. (Educological discourse, 2015)
In article defines the content, stages and levels of professional competence formation technology of employees’ employment centers. The specificity components of professional competence of employees’ employment centers. The investigation of assessing the professional competence of employee’s local employment centers. Proved a competency based approach as a reaction personnel training system to change social and economic conditions and the processes that are caused by development of a market economy.